Valuation analysis to determine fair market value of sft hotel the company case study: subsidaries companies of apl (period 2014-2017) - Ferdo, Redian; Sukarno, Subiakto (The Indonesian Journal of Business Administration, 2018)
As the number of branded hotels in Indonesia increase significantly which lead more investor and business owner to see opportunity to purchase well-designed and well managed hotels. That means the owner will be thinking more about the valuation of the hotels. How much is the business really worth is the main question of this research, the main purpose of this analysis is to find the market value of the business. APL is the biggest player in property developer in Indonesia with experience more than 40 years. The company has played significant role in developing luxurious property market in Indonesia including hotel, office, house and apartment. As with the growing number of property developed by APL which lead the company to sell their business segment in order to gain more capital to expand their area property of development.  This research using secondary data without gaining information directly from the company. This analysis using discounted cash flow analysis to determine the value of the company. During the analysis, this research using several financial performance analysis including their financial historical year on year, ratio analysis and projection analysis.Keywords: Valuation, Hotel, Market Value